An alginate-poly(acrylamide) hydrogel with TGF-beta 3 loaded nanoparticles for cartilage repair: Biodegradability, biocompatibility and protein adsorption - AKAKIN, DİLEK; ALARÇİN, EMİNE (ELSEVIER, 2021)
Current implantable materials are limited in terms of function as native tissue, and there is still no effective clinical treatment to restore articular impairments. Hereby, a functionalized polyacrylamide (PAAm)-alginate (Alg) Double Network (DN) hydrogel acting as an articular-like tissue is developed. These hydrogels sustain their mechanical stability under different temperature (+4 degrees C, 25 degrees C, 40 degrees C) and humidity conditions (60% and 75%) over 3 months. As for the functionalization, transforming growth factor beta-3 (TGF-beta 3) encapsulated (NPTGF-beta 3) and empty poly(lactide-co-glycolide) (PLGA) nanopartides (PLGA NPs) are synthesized by using microfluidic plat-form, wherein the mean particle sizes are determined as 81.94 +/- 92 nm and 126 +/- 4.52 nm with very low poly-dispersity indexes (PDI) of 0.194 and 0.137, respectively. Functionaliza lion process of PAAm-Alg hydrogels with ester-end PLGA NPs is confirmed by MR analysis, and higher viscoelastidty is obtained for functionalized hydrogels. Moreover, cartilage regeneration capability of these hydrogels is evaluated with in vitro and in vivo experiments. Compared with the PAAm-Alg hydrogels, functionalized formulations exhibit a better cell viability. Histological staining, and score distribution confirmed that proposed hydrogels significantly enhance regeneration of cartilage in rats due to stable hydrogel matrix and controlled release of TGF-beta 3. These findings demonstrated that PAAm-Alg hydrogels showed potential for cartilage repair and clinical application. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Alginate; Articular cartilage; Double network hydrogels; Nanoparticles; Growth factor